An Investigation of Internet Users’ Attitudes to Targeted Internet Advertising - Webb, Luke PC (2009)
New technologies, especially in relation to web marketing, have created a marketing watershed in terms of opportunities for marketers to target and personalise advertising to internet users. The purpose of this project is to explore to what extent this type of marketing has, in some cases, led to psychological concerns amongst consumers. The attitudinal dimensions of control, privacy and trust are emphasised within the literature and a comparative survey of 64 internet users is conducted and analysed, focusing on these framed attitudes in relation to the marketing on Amazon.com and Facebook.com. The results show specific concerns do exist in regard to the contextualised target marketing processes. It is concluded that marketers must be careful to respect internet users’ privacy and ethical rights in their search for marketing economic efficiency, with fears surrounding personal information and marketing manipulation increasingly apparent.